Protection of Photoanodes Against Photo-Corrosion by Surface Deposition of Oxide Films: Criteria for Choosing the Protective Coating - G. Campet; J. P. Manaud; C. Puprichitkun; Z. W. Sun; P. Salvador (Active and Passive Electronic Components)
Two strategies to solve the problem of instability of photoanodes against photocorrosion have been explored. The photocorrosion of photoanodes generally occurs when they enter the fabrication of efficient photoelectrochemical cells (i.e. showing high values of the open circuit voltage and photocurrent density).